EKSPLORASI DAN KARAKTERISASI BAKTERI ENDOFIT DARI TANAMAN KOPI SOLOK RADJO, SUMATERA BARAT - Diana Putri; Arifda Ayu Swastini Waruwu; Sri Heriza; Zahlul Ikhsan (Agriculture Faculty of Flores University, 2026)
Endophytic bacteria in a plant tissue do not cause disturbance or damage to the plant. Phytohormones produced by endophytic bacteria can increase plant growth and function as antimicrobials. The study aims to explore, select, and characterize the morphology of endophytic bacteria originating from the stems and roots of coffee plants from Solok Radjo. Morphological observations were carried out after obtaining a single isolate of endophytic bacteria, then a Gram test with 3% KOH and a hypersensitive reaction test on water henna plants were carried out to determine the pathogenicity of the endophytic bacteria. A total of 35 isolates were obtained from the isolation results, namely 23 isolates from the stem and 12 isolates from the roots. The results of morphological observations of endophytic bacterial colonies on Nutrient Agar (NA) media were dominated by irregular colony shapes, smooth and shiny surfaces, flat elevations, and yellowish-white colony colors. Gram testing with 3% KOH obtained 17 isolates classified as Gram-positive and 18 isolates as Gram-negative. Hypersensitive observations that showed symptoms of necrosis (positive reaction) were 19 isolates, and no symptoms of necrosis (negative reaction) were 16 isolates.